Sensitivity of the STAT-VIEW rapid self-test and implications for use during acute HIV infection. (23rd August 2017) - Boukli, Narjis; Boyd, Anders; Wendremaire, Noémie; Girard, Pierre-Marie; Bottero, Julie; Morand-Joubert, Laurence
Abstract : Objectives: HIV testing is an important step towards diminishing incident infections. Rapid self-tests whose use is becoming more common in France could help increase access to testing, yet could fail to diagnose HIV during acute HIV infection (AHI). The aim of the present study was to evaluate HIV-detection sensitivity of a commonly used rapid self-test (STAT-VIEW HIV1/2), compared with another point-of-care rapid test (INSTI), among patients presenting with AHI. Methods: Individuals tested at Saint-Antoine Hospital (Paris, France) with negative or indeterminate western blot (WB) results and detectable HIV-RNA were included. Rapid tests were performed retrospectively on stored serum. Patients with and without reactive rapid tests were compared, while probability of having a reactive test was modelled across infection duration using logistic regression. Results: Of the 40 patients with AHI, 23 (57.5%) had a reactive STAT-VIEW rapid test. Patients with non-reactive versus reactive tests had a significantly shorter median time since infection (p=0.01), time since onset of symptoms (p=0.009), higher proportion with Fiebig stage III versus IV (p=0.003), negative WB results (p=0.007), higher HIV-RNA levels (p=0.001) and lower CD4+ and CD8+ cell count (p=0.03, p<0.001, respectively). When examining sensitivity over the course of AHI duration, the probability of HIV detection was 75.5% at 5 weeks from HIV transmission. The INSTI provided similar results with respect to proportion of reactive tests (62.5%), determinants for non-reactive test and probability of HIV detection at 5 weeks of infection (85.0%). Conclusions: Over half of AHI patients had reactive serology using the STAT-VIEW rapid self-test when performed on serum samples. Considering that detection sensitivity increased substantially over infection time, individuals should not rely on a negative result to accurately exclude HIV infection within at least 5 weeks of potential HIV exposure. Notwithstanding strong recommendations against rapid test use during AHI, some utility in detecting HIV is observed 5–12 weeks after transmission.